A systematic review on the effectiveness of herbal interventions for the treatment of male infertility - Shahid, Muhammad Nabeel; Afzal, Hassaan Shahzad; Farooq, Bareerah; Yousaf, Muhammad Rehan; Ijaz, Muhammad Rauf; Shafqat, Talha Ali; Khan, Tahir Mehmood; Neoh, Chin Fen; Lean, Qi Ying; Bukhsh, Allah; Karuppannan, Mahmathi (Frontiers in Physiology, 2022)
Background: Male infertility is an emerging health issue in the world today. Surgical interventions for the treatment of male infertility are available but are quite expensive. Herbal interventions pose a popular alternative for the treatment of infertility. However, much has to be learned regarding their safety and efficacy. Objective: To investigate the efficacy of herbal interventions in male infertility and also assess the possibility of these interventions as complementary and alternative medicine (CAM) in the future. Method: From inception till 16 December 2021 all articles emphasizing the efficacy of herbal interventions in the treatment of male infertility are included in this review. 7 databases are searched. The literature obtained is screened and extracted. Semen parameters, hormonal concentration and conception are the outcomes of interest. Results: 20 articles were included in this review. Herbal interventions might improve semen parameters in males with infertility. Among all the interventions, Hochu-ekki-to and W. somnifera have shown the most promising results and should be studied further in a larger sample size. Conclusion: This systematic review has demonstrated the efficacy of herbal interventions especially Hochu-ekki-to & W. somnifera in treating male infertility.